Upaya Peningkatan Hasil Belajar Pada Pembelajaran IPS Menggunakan Model Pembelajaran Kooperatif STAD: Indonesia - Farida (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to improve student learning outcomes through the STAD cooperative learning method. This research was applied to class IV SD Negeri No. 25 Air Tambang, Ranah Pesisir District, Pesisir Selatan Regency. This research is a classroom action research that uses a qualitative approach. The research design consisted of four components, namely: planning, implementation, observation, and reflection. Collecting data in this study using observation sheets and student learning outcomes obtained by giving tests to students, carried out in cycles. The results of the research in cycle 1 obtained a percentage of learning completeness 30% and in the second cycle, there was an increase in learning completeness by 77%. Based on the actions and results taken, it can be concluded that social studies learning through the cooperative learning model type STAD (Student Teams Achievement Division) can improve the learning outcomes of class III students of SDN No 25 Air Tambang, Ranah Pesisir District, Pesisir Selatan Regency.